The Effect of Work Stress and Cyberloafing Behavior on Employee Performance at Waled Regional General Hospital - Feni Nursuklan; Lisa Harry Sulistiyowati (Interdisciplinary Social Studies, 2026)
This study aims to analyse the influence of work stress and cyberloafing behaviour on the performance of employees at Waled Hospital, Cirebon Regency, both partially and simultaneously. The study population comprises 233 non-medical permanent employees of Waled Hospital, Cirebon Regency. The sample size was determined using the Slovin formula, yielding a sample of 148 respondents. Data were collected through a directly administered questionnaire using a Likert scale, while data analysis employed simple linear regression and multiple linear regression using IBM SPSS version 26. The results showed that work stress had a negative and significant effect on employee performance, as evidenced by a calculated t-value of ?11.465 and a significance level of 0.000 < 0.05. Cyberloafing behaviour also had a negative and significant effect on employee performance, with a calculated t-value of ?3.159 and a significance level of 0.002 < 0.05. Simultaneously, work stress and cyberloafing behaviour had a significant combined effect on employee performance, as evidenced by an F-value of 313.430 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.812 indicated that 81.2% of the variation in employee performance can be explained by work stress and cyberloafing behaviour, with the remainder attributed to other factors outside the scope of this study. The conclusion of this study is that work stress and cyberloafing behaviour are important factors affecting the performance of employees at Waled Hospital, Cirebon Regency. Hospital management therefore needs to manage work stress effectively and exercise control over cyberloafing behaviour in order to improve both employee performance and the quality of health services provided.